2021
DOI: 10.7759/cureus.17379
|View full text |Cite
|
Sign up to set email alerts
|

Port-a-Cath Insertion in Pediatric Patients With Malignancy in Tabuk

Abstract: Objectives A port-a-cath has become the cornerstone of supportive care and therapy for most childhood malignancies. It is routinely used in children for recurrent blood sampling or intravenous therapies. This study aimed to investigate the complications of port-a-cath insertion in children, the reasons for its removal or reinsertion, and to compare open and percutaneous techniques of insertion in pediatric patients with cancer in the northwest region of Saudi Arabia. Materials and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…While there are no published studies to date which evaluate the insertionrelated infection rates for radiologically placed ports in the pediatric population, multiple observational studies looking at complications of radiologically placed pediatric ports have found overall infection rates ranging from 2.56 to 14%. [13][14][15] The markedly higher infection rate in our pediatric population may be due to the anecdotally higher number of comorbidities in pediatric population specific to that large academic hospital when compared to adults. Future studies are needed to evaluate port insertion-related infectious rates in the pediatric population and whether prophylactic antibiotics are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…While there are no published studies to date which evaluate the insertionrelated infection rates for radiologically placed ports in the pediatric population, multiple observational studies looking at complications of radiologically placed pediatric ports have found overall infection rates ranging from 2.56 to 14%. [13][14][15] The markedly higher infection rate in our pediatric population may be due to the anecdotally higher number of comorbidities in pediatric population specific to that large academic hospital when compared to adults. Future studies are needed to evaluate port insertion-related infectious rates in the pediatric population and whether prophylactic antibiotics are indicated.…”
Section: Discussionmentioning
confidence: 99%